Decision support, analytics, and business intelligence - Power, Daniel J. (New York, : Business Expert Press, 2013)
Competition is becoming more intense. Decision makers are encountering increasing complexity, rapid change and higher levels of risk. In many situations, the solution is more and better computerized decision support, especially analytics and business intelligence. Today managers need to learn about and understand computerized decision support. If a business is to succeed, managers must know much more about information technology solutions. This introductory text is targeted to busy managers and MBA students who need to grasp the basics of computerized decision support, including: What is analytics? What is a decision support system? How can managers identify opportunities to create innovative computerized support? Overall this resource addresses 61 fundamental questions relevant to understanding the rapidly changing realm of computerized decision support. In a short period of time, readers can'get up to speed' on decision support, analytics and business intelligence. The text then provides a quick reference to important recurring questions.
Acknowledgments -- Introduction -- 1. Modern decision support -- 2. Decision support concepts -- 3. Recognizing types of decision support -- 4. Business intelligence and data-driven DSS -- 5. Predictive analytics and model-driven decision support -- 6. Decision support benefits and trade-offs -- 7. Identifying decision support opportunities -- 8. Looking forward to innovative decision support -- Notes -- Glossary -- References and bibliography -- Index -- List of questions with links to answers.
Title from PDF t.p. (viewed Jan. 27, 2013).
Part of: 2013 digital library.
Includes bibliographical references (p. 149-156) and index.
Keywords: Decision support systems; analytics; business intelligence; decision support; decision support systems; decision making; knowledge management; computerized support; business applications; basic concepts; types of decision support; innovative DSS; Electronic books; Electronic books